Motivation and Cognitive Learning in Workplaces of Vietnamese Students in Learning Chinese: A Qualitative Study - Thuan Quan Kieu; Wei-Te Liu (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
In language learning, besides suitable learning strategies, motivation plays as the motor to encourage learners to walk toward their desired plans. Moreover, learning cognition in workplaces is considered as good strategies for language learning in off-classrooms. To comprehend the learning motivation and learning cognition in workplaces of language learners, this study aims to explore the motivation’s components and learning cognitions in workplaces of Chinese learners. Five Vietnamese students, who had studied Chinese at least for six months, were subjects of the study. Interviews and diary note-takings were used as the instruments for data collection. Data were analyzed through a descriptive analysis and coding categories. The obtained results showed that there are three major factors of motivation's components for participants to learn Chinese: (1) communicative purpose, (2) interest in culture and (3) promotion of future career. Moreover, in term of cognition of Chinese usage in workplaces, obtained results showed that the cognition of participants in two key procedures: knowing from problem-solving and reasoning and knowing from association with people in their workplaces.